Nucleon scattering analysis with a lane-consistent dispersive optical potential for Hf, W and Ta isotopes. (19th May 2021) - Zhao, Xiuniao; Sun, Weili; Soukhovitskiĩ, E Sh; Martyanov, D S; Quesada, J M; Capote, R
Abstract: Nucleon scattering on tungsten and neighboring nuclei are analyzed with a coupled-channels method based on a soft-rotator structure model. The multiple band couplings and nuclear stretching factors are built using nuclear wave functions of the soft-rotator model with the Hamiltonian parameters adjusted to reproduce the energy of low-lying collective levels of corresponding nuclei. A regional lane-consistent dispersive coupled-channels optical-model potential is derived to reproduce the neutron total cross sections, nucleon elastic and inelastic scattering angular distributions, and analyzing powers. Excellent agreement with measurements is obtained for neutron total cross sections of 182, 183, 184, 186 W, 178 Hf, and 181 Ta targets in the whole energy range from 100 keV to 200 MeV; other scattering data are found to be in good agreement with measurements. A deformation-dependent nuclear radius correction arising from the volume conservation condition is introduced and allowed to remove phenomenological radii dependencies on nuclear mass from the potential geometry.